Safety Stock Information Dashboard of Hospital Pharmaceutical Inventory in integration with Indonesia National Health Insurance - Priyo Nugroho Adi; Susana Ayu Handayani; Toni Prahasto (Elkom : Jurnal Elektronika dan Komputer, 2020)
In all section of inventory management, including inventory management in a hospital, minimize cost and ideal inventory accommodation against demand has always been a primary goal (Varghese, 2012). Nearly a third of the operational success of a hospital is in the field of medical supplies. In its usual way, inventory management in hospitals using the approach to the demand usage, the characteristics of the item and the estimate of the demand. The model presented in this study accommodates that common approach which use a combination of inventory safety stock limit, Economic Order Quantity, and reorder point in a information system dashboard that capable to provide quick and easy information about the condition of inventory management. The result of the system are used for the hospital pharmaceutical inventory management in integration with the INACBGs to optimize the inventory performance.